(untitled) (American Journal of Arts and Human Science, 2025)
This study explicates Paramātmā-Jnāna as presented in the Śrimad Bhāgavata Mahāpurāṇa, focusing on the intricate concept of divine immanence and the path of spiritual knowledge. Paramātmā, or the Supreme Soul, is understood as the omnipresent, all-pervading aspect of the Divine, existing within every living being and throughout the cosmos. In this article, interpretative method is used for the exploration of Paramātmā-Jnāna. The researcher uses the methodology of Swami Vevakananda’s principle on Paramātmā-Jnāna for the analysis of the text. This article concentrates on the significance of the philosophical and theological nuances of Paramātmā-Jnāna, examining how this spiritual wisdom emphasizes the realization of the Divine within oneself and the universe. Through textual analysis, the study highlights the Bhāgavata Mahāpurāṇa’s teachings on how contemplative practices, devotion, and self-purification lead to the ultimate realization of Paramātmā. The analysis also situates these ideas within the broader context of Vedantic and Bhakti traditions, emphasizing the synthesis of knowledge (jñāna) and devotion (bhakti) as a means to transcendental understanding. The findings of the investigation indicate that the concept of Paramātmā-Jnāna emphasizes the realization of the Divine presence within all beings, illustrating the immanence of God and the profound spiritual knowledge necessary to comprehend the unity between the individual soul (jīvātman) and the Supreme Soul (Paramātmā). The main conclusion drawn from this investigation is Paramātmā-Jnāna in the Śrimad Bhāgavata Mahāpurāṇa reveals a profound understanding of divine immanence and spiritual knowledge, emphasizing the intimate presence of the Supreme Soul within all beings and the path to realize this divine connection through devotion and wisdom.